Masturbation in male capped langurs (Trachypithecus pileatus) at Lawachara National Park, Bangladesh - Hasan, Sabit; Nath, Shimul; Ahmed, Md Toufique; Tasnim, Mahia; Biswas, Sajib; Hossain, Md Sakhawat; Ahmed, Tanvir (Bangladesh Journal of Zoology, 2022)
Abstract not available Bangladesh J. Zool. 49 (3): 441-445, 2021